Peran Antroplogi Bagi Studi Islam - Leni, Nurhasanah (Analisis: Jurnal Studi Keislaman, 2018)
This understanding makes Islamic studies less developed and unable to reach the religious practices of Muslims themselves. This article aims to describe the contribution of anthropology in Islamic studies. This article is a literature review by analyzing books related to Islamic studies and anthropology. The results of the study show that anthropology has at least two main functions for Islamic studies, namely helping Islamic studies in understanding the empirical aspects of Muslim diversity and helping to see the diversity of cultural influences in the practice of Islamic teachings. Furthermore, this study concludes that anthropology has a positive contribution to the development of Islamic studies